Prekancerózy v gynekologii - pochva - Feranec, R; Mouková, L; Chovanec, J (Klinicka onkologie, 2013)
Preinvasive lesions of the vagina are relatively rare, clearly defined afflictions, originating most of all in association with the highrisk human papillomavirus infection (HR HPV). The most frequent appearance is in coincidence with preinvasive lesions of uterine cervix and in vaginal cuff after hysterectomy. Preinvasive vaginal lesions are divided into squamous lesions (vaginal intraepithelial neoplasia) and nonsquamous lesions. Vaginal adenosis belongs to nonsquamous vaginal preinvasive lesions and is a precursor lesion of vaginal clear cell carcinoma. Surgical and nonsurgical techniques including laser destructive methods and local administration of 5- fluorouracile are used in the treatment of preinvasive lesions of vagina.
Keywords: Vaginal Neoplasms; infekce papilomavirem; Uterine Cervical Neoplasms; Female; nádory vaginy; Papillomavirus Infections; preinvasive lesion - vagina - vaginal intraepithelial neoplasia - vaginal adenosis; nádory děložního čípku; prekancerózy; ženské pohlaví; Humans; Precancerous Conditions; lidé